Eficiencia agronómica de fertilizantes nitrogenados y potásicos, sobre el comportamiento agronómico del arroz (Oryza sativa) bajo riego en la zona de Babahoyo - Ochoa Jara, Denys Asael (2020)
The experimental work was carried out on the grounds of the "Palmar" Experimental Farm owned by the Technical University of Babahoyo., In the Babahoyo canton, the variety of rice used was SFL-11, in which the effect of the application of potassium and nitrogen based fertilizers on irrigated rice production. With this, the effects of the doses of the products on the agronomic behavior and an economic analysis of the grain yield based on the cost of the treatments were evaluated. The randomized complete blocks experimental design was used, with 11 treatments and three repetitions. Variables were evaluated: plant height, number of tillers, number of panicles, length of panicles, number of grains per panicle, weight of 1000 grains, days to flowering, days to harvest, grain yield, partial productivity per nutrient and analysis. economic. The evaluated variables were exposed to the analysis of variance, and the Tukey test was applied at 5% significance to determine the statistical difference between the means of the treatments. Observing the experimental results, no statistical significance was achieved in the number of tillers, number of panicles, length of panicles, days to flowering and number of grains. Plants with higher height were obtained by applying 300 kg/ha Urea + Potassium Muriate 150 kg/ha. The highest yield was reflected by applying Urea 300 kg/ha + Potassium Muriate 150 kg/ha. Treatment Urea 300 kg/ha + Potassium Muriate 150 kg/ha achieved the greatest benefit with $ 883.99. Higher PPN values were achieved by applying Urea 300 kg/ha + Potassium Muriate 150 kg/ha.